(untitled) (Journal of Parents and Teachers, 2026)
Jesús Garrido Suárez describes how group dynamics can be analysed and evaluated in parent schools and educational settings. An example of a group selfassessment document combining three strategies is provided. The author highlights the importance of the group feeling identified and being able to self-assess in order to improve its functioning.